Serum Amyloid A as a possible marker of health and disease in non-domesticated mammals - Lundin, John-Filip (2015)
The veterinary handling of wildlife, both in zoos and in the wild, commonly requires that the patients need to be captured and immobilized for examination or treatment. This emphasises the need for quick, on-site, laboratory equipment, in order to minimize the analysis time and thus the stress for the animal and also in order to increase the possibility of starting relevant treatment early on. The aim of this pilot study was to determine whether Serum Amyloid A (SAA) could be a measured in blood samples from bottlenose dolphins (Tursiops truncatus), Asian elephants (Elephas maximus) and South American tapirs (Tapirus terrestris). SAA rises to its maximum about 24 hours after the introduction of an inflammatory agent in companion animals. This also correlates with the estimated time it takes for animals at Kolmården Wildlife Park to be examined and having blood samples collected after being observed as sick. The study also evaluated whether the Eurolyser SOLO, using a turbidometric immunoassay (TIA) developed for human diagnostics, could be used for such analysis. This pilot study was a retrospective analysis of SAA in convenience sampled frozen serum, collected from dolphins, elephants and tapirs. Eight (8) samples were analysed from presumed sick individuals of each species with systemically inflammatory symptoms. Those samples were compared to eight (8) samples collected from presumed healthy individuals of each species. Due to limited serum supply, some individuals were used for several serum samples. The serum samples had been stored in frozen in the serum bank at Kolmården Wildlife Park, and they had all been collected from animals within the zoo. All analyses were performed using the Eurolyser SOLO analyser, provided by Triolab. The study showed that it is possible to use the Eurolyser SOLO and the turbidometric method for the analysis of SAA in the selected wildlife species, although, validation research is needed. SAA values from the presumed healthy dolphins ranged between 30,8-66,2 g/mL and values from presumed sick dolphins ranged between 21,0-66,3 g/mL. SAA values from presumed healthy tapirs ranged between 33,2-53,8 g/mL, plus one that was <10,0 g/mL, and the values from presumed sick tapirs ranged between 16,8-52,3 g/mL. It would be interesting to analyse other acute phase proteins in the three species in order to identify other suitable and useful indicators of inflammatory disease. The highest value was >500,0 g/mL SAA in one sample from a presumed sick elephant. Limitations of the study includes a small sample size, the unknown effects of storage on the SAA levels and the lack of a gold standard for SAA analysis in these species. These factors must be controlled in a proper validation study. In the future, more research ought to be made in order to identify the clinically relevant acute phase proteins for each species handled at zoos and in the wild. Given the availability of the extensive serum bank and the number of animals that are examined every day, such a study could provide much useful information.